Lego robot toys emoticon / Norazlin Mohamad … [et al.] - Mohamad, Norazlin; Che Mood, Aslinda; Che Othaman, Nor Nazihah; Belayong, Cindy (Division of Research and Industry Linkages, 2017)
Autism Spectrum Disorder (ASD) consists of autistic disorder, Asperger syndrome and Pervasive Developmental Disorder, ASD is known as neurodevelopment disorder which causes the significant of social, communication and behavioural challenges. Children with ASD usually having problems in developing expression, language and motor skills either in fine motor skills or gross motor skills. A study by Libertus, Sheperd, Ross & Landa (2014) proposed that there is reducing in grasping and fine motor skills among six-months-old infants at increased of genetic risk for ASD. LeBarton & Iverson (2013) found that children with ASD have relationship between the fine motor activities and the expressive language. To overcome this problem, it is necessary to understand the common symptoms and design suitable strategies that can help the children in this domain which developing the fine motor skills and expressing emotion. Nowadays many devices and program applications are invented to make life easier. This innovation is an application that is designed specifically to provide the needs of children with ASD though it appeals to children with all ages, The primary function is to identify the emotion among the children with ASD. Secondary functions consist of sensory issues and fine motor skills where the children with ASD have their own favourite material to touch such as soft surface and fuzzy. It is an application provided with six interchangeable geometric-shaped heads emotions featuring with the music according to the emotion and a range of textures to shows the sensory issues. It is important to show the designing of Lego toys that meet the needs of ASD children without looking like a special needs toy. The Lego robot is a toy that encourages the children with ASD in progressing their expression emotion and also the fine motor skills. It is different with other Lego toys which they didn’t have music and the texture of the surface aIso different.